Current Concepts in the Management of Necrotizing Fasciitis - Misiakos, Evangelos P.; Bagias, George; Patapis, Paul; Sotiropoulos, Dimitrios; Kanavidis, Prodromos; Machairas, Anastasios (Frontiers in Surgery, 2014)
Necrotizing fasciitis is a severe, rare, potentially lethal soft tissue infection that develops in the scrotum and perineum, the abdominal wall or the extremities. The infection progresses rapidly, and septic shock may ensue; hence, the mortality rate is high (median mortality 32.2%). Prognosis becomes poorer in the presence of co-morbidities, such as diabetes mellitus, immunosuppression, chronic alcohol disease, chronic renal failure and liver cirrhosis. Necrotizing fasciitis is classified into four types, depending on microbiological findings. Most cases are polymicrobial, classed as type I. The clinical status of the patient varies from erythema, swelling and tenderness in the early stage to skin ischemia with blisters and bullae in the advanced stage of infection. In its fulminant form, the patient is critically ill with signs and symptoms of severe septic shock and multiple organ dysfunction. The clinical condition is the most important clue for diagnosis. However, in equivocal cases, the diagnosis and severity of the infection can be secured with laboratory-based scoring systems, such as the LRINEC score or FGSI score, especially in regard to Fournier’s gangrene. Computed tomography or ultrasonography can be helpful, but definitive diagnosis is attained by exploratory surgery at the infected sites. Management of the infection begins with broad spectrum antibiotics, but early and aggressive drainage and meticulous debridement constitute the mainstay of treatment. Postoperative management of the surgical wound is also important for the patient’s survival, along with proper nutrition. The vacuum-assisted closure system has proved to be helpful in wound management, with its combined benefits of continuous cleansing of the wound and the formation of granulation tissue.